Effect of dehydroepiandrosterone administration in Chinese women over 37 years undergoing assisted reproductive techniques. (July 2016) - Liu, Xuemei; Wang, Wenjuan; Wang, Xinrong; Qu, Qinglan; Hao, Cuifang
Abstract: Objective: To evaluate the effect of DHEA supplementation on in vitro fertilization (IVF) parameters and pregnancy outcomes in patients older than 37 years with normal ovarian reserve. Study design: A retrospective cohort study was conducted to evaluate the impact of DHEA supplementation on IVF outcome of infertile women over 37 years with normal ovarian reserve between January 2012 and July 2014. 243 patients (study group) received 75 mg of DHEA daily (25 mg three times daily) before the IVF cycle. Another 243 patients (control group) received infertility treatment, but did not receive DHEA. The IVF outcome parameters in each group were compared. Results: Both groups did not show statistically significant differences in terms of patient demographics characteristics, mean numbers of oocytes retrieved and mature oocytes rate. While patients in the DHEA group have the significantly higher implantation rate and live birth rate compared with controls (30.13% versus 22.70%, 43.33% versus 28.26%). We also found that the cycle cancellation rate and miscarriage rate were lower in the DHEA group (1.23% versus 5.34%, 13.33% versus 28.89%). Conclusion: DHEA supplementation may significantly improve IVF outcomes in infertile women over the age of 37.